(untitled) (Medico Legal Update, 2020)
This study aims to determine the factors associated with the presence of Aedes aegypti larvae in endemic and nonendemic areas of DHF in Biringkanaya District. The type of research used was observational with cross sectional design and through direct observation. The population is all houses in the Village of Pai and Kelurahan Daya. Determination of the sample was carried out by proportional simple random sampling method in order to obtain a sample of 100 houses each. Data analysis was carried out was univariate and bivariate with chi square test. The results showed that the related variables were the actions of PSN in endemic areas (p = 0.025), water temperature (p = 0.000), house humidity (p = 0.000), container conditions (p = 0.000) in endemic areas and (p = 0.002) in nonendemic areas. Unrelated variables are knowledge (p = 0.141) in endemic areas and (p = 0.824) in nonendemic areas. The conclusion of this study is that there is a relationship between PSN action, water temperature, house humidity, and container conditions with the presence of larvae in endemic areas, but there is no relationship between respondents’ knowledge in the two regions and the actions of PSN in nonendemis areas.